Environmental perception in the solid waste context (Research, Society and Development, 2022)
This article aimed to analize a environmental perception of the school community of a Federal Institute of Education Campus regarding the environmental problems arising from solid waste. In the research, questionnaires were used with closed and/or open questions. The sample consisted of 25% of teachers and 40% of students in the Technical Logistics Course; 45% of administrative technicians and 55% of outsourced. In research, Society appears as the main responsible for the environment and, for the most part, considers its responsibility in the disposal of the generated waste. The results also indicated that education, professional category and gender do not influence in a way that increases the individual’s perception. Although some means and medians. When analyzed separately, point to a slight increase in perception, this is not capable of guaranteeing, whit sufficient certainty, a structural pattern. It was also observed the relevance of such information to support the management, construction of indicators for monitoring, communication and evaluation of waste, and for the design of teaching materials.